Peranan Kompetensi Kerja Terhadap Kepuasan Kerja Dan Kinerja - Dellia Mila Vernia; Loecita Sandiar (Peneliti.net, 2020)
The existence of humans in organizations has a very vital position, organizational success is largely determined by the quality of the people who work in it. organizations are not only able to provide satisfying services but are also oriented to values, so organizations can achieve maximum performance in the process of achieving it. Consequently, organizations need human resources who have unique skills and abilities in accordance with the organization's vision and mission. Competency-based human resource development is carried out in order to provide results that are in accordance with the goals and objectives of the organization with established performance standards. The phenomenon that occurs in the field shows that the ability of human resources is still limited, this is evidenced by the existence of workforce data whose education level does not match the type occupation. In performance management, competence plays a role in individual behavior in adjusting work properly. Therefore it is felt necessary to explore more about the role of human resource competencies to create job satisfaction and improve employee performance in the company